Subdoses de glyphosate no desenvolvimento de espécies arbóreas nativas - Pereira, Maria Renata Rocha; Souza, Guilherme Sasso Ferreira de [UNESP]; Fonseca, Edson Diniz; Martins, Dagoberto [UNESP] (Univ Federal Uberlandia, 2015)
Recovery of degraded areas aims to provide the degraded environment favorable conditions for restructuring in an environment that is unable to regenerate itself and planting of tree seedlings is one of the effective ways to extend this process. However, native tree species have slow growth rate which increases the seedlings production time as well as decreases their competitiveness with weeds in areas of forests deployment. The aim of this study was to evaluate the effects of glyphosate reduced rates application on Psidium cattleyanum (yellow guava), Citharexylum myrianthum (pau-viola) and Cedrela odorata (cedro) seedlings development by analyzing its morphophysiological parameters. The experiment was carried out in greenhouse conditions and the experimental units consisted of one plant were conducted in 2.5L plastic pots and arranged in a completely randomized design with six replications. Treatments consisted of glyphosate application at 0, 7.5, 15, 30 and 60 g ha(-1) using Scout (R) commercial formulation. Treatments application on these species seedlings was realized 120 days after seeds germination. Visual evaluations of plants phytotoxicity were realized at 7, 14 and 21 days after treatments application and plants survival, stomatal conductance, height, stem diameter and dry mass of shoots were evaluated 90 days after treatments application. Different doses of glyphosate did not cause plants phytotoxicity. Already, 30 and 60 g ha(-1) of glyphosate provided greater increases in height, stem diameter and dry mass of shoots for Citharexylum myrianthum and Psidium cattleyanum, respectively.

A recuperação de áreas degradadas tem o objetivo de fornecer ao ambiente degradado condições favoráveis a reestruturação em um ambiente que não tem condições de se regenerar por si só, sendo o plantio de mudas arbóreas uma forma efetiva de ampliar este processo. Entretanto as espécies arbóreas nativas têm ritmo de crescimento lento, o que aumenta o tempo da produção da muda, como também diminui a competitividade destas com as plantas daninhas em áreas de implantação de florestas. O objetivo deste estudo foi avaliar os efeitos da aplicação de subdoses de glyphosate no desenvolvimento de mudas de Psidium cattleyanum (araçá-amarelo), Citharexylum myrianthum (pau-viola) e Cedrela odorata (cedrinho), através da análise de seus parâmetros morfofisiológicos. O experimento foi instalado e conduzido em casa de vegetação, e as unidades experimentais foram constituídas de uma planta, conduzida em vasos com capacidade para 2,5L, dispostos inteiramente ao acaso, arranjados em uma esquema fatorial (doses x espécies), com seis repetições. Os tratamentos foram constituídos da aplicação herbicida glyphosate nas seguintes subdoses: 0; 7,5; 15; 30 e 60 g e.a. ha-1, na formulação comercial Scout®. A aplicação nas mudas foi realizada aos 120 dias após germinação. Foram realizadas avaliações dos efeitos dos tratamentos químicos (fitointoxicação) sobre as plantas aos 7, 14 e 21 dias após aplicação, e após 90 dias foram avaliados a sobrevivência das plantas, condutância estomática, altura, diâmetro do caule e massa seca de parte aérea. As diferentes doses do herbicida não provocaram intoxicação às plantas. Já a dose de 30 e 60 g e.a. ha-1 proporcionou maiores incrementos em altura e diâmetro, bem como maiores massas secas em plantas de pau-viola e araçá-amarelo, respectivamente.
Glyphosate reduced rates on the development of native tree species
Keywords: Psidium cattleyanum; Citharexylum myrianthum; Cedrela odorata; Herbicide; Psidium cattleyanum; Citharexylum myrianthum; Cedrela odorata; Herbicida